2019
DOI: 10.1038/s41467-019-13540-4
|View full text |Cite
|
Sign up to set email alerts
|

The autophagy receptor p62/SQST-1 promotes proteostasis and longevity in C. elegans by inducing autophagy

Abstract: Autophagy can degrade cargos with the help of selective autophagy receptors such as p62/SQSTM1, which facilitates the degradation of ubiquitinated cargo. While the process of autophagy has been linked to aging, the impact of selective autophagy in lifespan regulation remains unclear. We have recently shown in Caenorhabditis elegans that transcript levels of sqst-1/p62 increase upon a hormetic heat shock, suggesting a role of SQST-1/p62 in stress response and aging. Here, we find that sqst-1/p62 is required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 67 publications
8
86
1
1
Order By: Relevance
“…Unc-51-like kinase 1 (ULK1) is a cytoplasmic kinase that is important to the process of autophagy. It is a homologue of ATG1 gene in mammals, with a total similarity of 29% [22,23]. It has been shown that ULK1 can either promote or inhibit tumor growth through protein-protein interactions and post-translational modification-mediated autophagy in nutrient-deficient environments [24].…”
Section: Introductionmentioning
confidence: 99%
“…Unc-51-like kinase 1 (ULK1) is a cytoplasmic kinase that is important to the process of autophagy. It is a homologue of ATG1 gene in mammals, with a total similarity of 29% [22,23]. It has been shown that ULK1 can either promote or inhibit tumor growth through protein-protein interactions and post-translational modification-mediated autophagy in nutrient-deficient environments [24].…”
Section: Introductionmentioning
confidence: 99%
“…Our results, therefore, indicate that p62 downregulation is associated with senescent phenotypes. In fact, p62 has recently been associated with longevity and its absence to aging in C. elegans [25]. We propose that FAK inhibition may be a valid strategy to counteract GBM progression through senescence deregulation.…”
Section: Discussionmentioning
confidence: 85%
“…Strikingly, the bioinformatic analysis led to a list of only 20 genes that interact with genes mutated in fALS. One of them, SQSTM1/p62, a known regulator of autophagy (28), associates with the four fALS genes included in our analysis and is up-regulated in 4.5-month-old En1-Het mice injected at 3 months with an inactive form of EN1, but is normal in En1-Het mice injected with active EN1. The ensuing hypothesis that En1 may interact with fALS genes will be evaluated by generating double heterozygotes for En1 and fALS genes.…”
Section: Homeoproteins Act Cell-and Non-cell-autonomously a Strictlymentioning
confidence: 93%
“…However, although they may exist in some sporadic cases, no ALS phenotype has been associated with mutations affecting EN1 expression, precluding that the En1-Het mouse be considered as an ALS model. Yet, En1 might interact genetically with pathways leading to ALS, and EN1 could be envisaged as a long-lasting therapeutic protein, as shown in classical mouse and non-human primate models of Parkinson Disease (28).…”
Section: Homeoproteins Act Cell-and Non-cell-autonomously a Strictlymentioning
confidence: 99%